Effect of folic acid and vitamin B12 plus rosuvastatin in the treatment of coronary heart disease combined with hyperlipidemia - Wang, Hao; Wang, Tiezheng (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo explore the effect of folic acid and vitamin B12 plus rosuvastatin in treating coronary heart disease (CHD) complicated with hyperlipidemia.MethodsOne hundred CHD patients combined with hyperlipidemia admitted to our hospital from January 2022 to December 2023 were separated into study group as well as control group. The control group accepted rosuvastatin calcium tablets. The study group received rosuvastatin plus folic acid and vitamin B12. The cardiac function, blood lipid, plasma Hcy, folate and vitamin B12 levels, inflammation, clinical effect along with occurrence of adverse reactions were compared in 2 groups.ResultsCompared to before therapy, LVEDD and LVESD levels were declined while LVEF level was elevated in 2 groups after therapy, TC, TG and LDL-C levels were declined while HDL-C level was elevated in 2 groups after therapy, plasma Hcy level was declined while folate and vitamin B12 levels were elevated in 2 groups after therapy, and IL-6, TNF-α along with CRP levels were declined in 2 groups after therapy. Compared to control group, the improvements of the above cardiac function indicators, blood lipid indexes, plasma Hcy, folate and vitamin B12 levels, serum inflammatory markers in the study group were more apparent, the total effective rate in the study group presented better. No difference was seen in the occurrence of adverse reactions between 2 groups.ConclusionFolic acid and vitamin B12 plus rosuvastatin can effectively improve cardiac function, blood lipid, inflammatory response, and has high safety in treating CHD complicated with hyperlipidemia.